A select library of the Nicene and Post-Nicene Fathers of the Christian church - Schaff, Philip; Wace, Henry; Basil the Great, Saint, Archbishop of Caesarea (Edinburgh, Scotland T and T Clark, 1889)
Includes bibliographical references and indexes.
V. VIII contains letters and select works of St Basil the Great, Archbishop of Caesarea
Keywords: Fathers of the church -- Primitive and early church -- ca 30-600